👤

efectuand (-5)⁰+(-5)¹+(-5)² este egal cu..?​

Răspuns :

Răspuns:

[tex]( - 5)^{0} + ( - 5)^{1} + ( - 5)^{2} [/tex]

[tex]1 - 5 + 25 = -4 + 25 = 21[/tex]

Explicație pas cu pas:

Bună!

Deci ni se cere efectuăm următoarea

[tex] {( - 5)}^{0} + {( - 5)}^{1} + { ( - 5)}^{2} = x [/tex]

[tex]x \:\in \: N[/tex]

➡️

Calculăm

[tex] {( - 5)}^{0} [/tex]

și obținem

1

[tex]1 + {( - 5)}^{1} = 1 - 5 = (- 4)[/tex]

și ultima dată, din nou efectuăm

[tex]( - 4) + {( - 5)}^{2} = (- 4 )+ 25 = 21[/tex]

Gataa <3

#copaceibrainly